Histopathologic characterization of the reproductive organs of heifers experimentally infected with Campylobacter fetus venerealis - Giobergia, María; Herrera, Marcela; Teruel, Miriam; Riccio, Belén; Catena, Maria (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Bovine campylobacteriosis is a venereal disease due to infection with Campylobacter fetus venerealis. It causes mainly reproductive failures that lead to considerable economic losses. Objective: To perform a histopathological description of the mucosa from reproductive organs of heifers experimentally infected with Campylobacter fetus venerealis. Methods: Twelve 15-18-months-old Aberdeen Angus heifers were treated for estrous synchronization and exposed to natural breeding. They were then randomly divided into two groups: group A (n=9) was inoculated with C. fetus venerealis; group B (n=3, control) was inoculated with a placebo. Ultrasonography was performed at days 29, 38, and 42 post-breeding, and plasmatic progesterone levels were quantified using ELISA to confirm pregnancies. Animals in group A with plasma progesterone levels below 1 ng/mL and/or diagnosed as non-pregnant were further divided into three subgroups: A1 (n=4), euthanized at day 30 post-breeding; A2 (n=3), euthanized at day 40 post-breeding and A3 (n=2), euthanized at day 55 postbreeding. Heifers from group B, all diagnosed as pregnant, were euthanized each at day 30, 40, and 55 days post-breeding as well. Histological sections from every group were taken from oviducts, uterus, and vagina. Results: Lymphocytic inflammation was the most common lesion in all infected heifers. Trophoblast cells were found in the non-pregnant heifers euthanized at days 40, and 55 post-breeding. The inflammatory process with the presence of lymphoid cells probably altered the balance in the activity of maternal lymphoid cells, as well as gene expression of the trophoblast, finally affecting the embryo survival. Conclusion: This work contributes to the understanding of the histopathological process involved in post-mating infection of Campylobacter fetus bovine.